Pregunta
upstudy study bank question image url

Solve the equation. \( \frac{4}{w^{2}+2 w-8}+\frac{5}{w^{2}+w-6}=\frac{4}{w^{2}+7 w+12} \)

Ask by Campbell Long. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( w = -8 \)

Solución

To solve the equation: \[ \frac{4}{w^{2} + 2w - 8} + \frac{5}{w^{2} + w - 6} = \frac{4}{w^{2} + 7w + 12} \] **Step 1: Factor the Denominators** 1. **Factor \( w^{2} + 2w - 8 \):** \[ w^{2} + 2w - 8 = (w + 4)(w - 2) \] 2. **Factor \( w^{2} + w - 6 \):** \[ w^{2} + w - 6 = (w + 3)(w - 2) \] 3. **Factor \( w^{2} + 7w + 12 \):** \[ w^{2} + 7w + 12 = (w + 3)(w + 4) \] **Step 2: Identify the Least Common Denominator (LCD)** The LCD of the denominators \((w + 4)(w - 2)\), \((w + 3)(w - 2)\), and \((w + 3)(w + 4)\) is: \[ \text{LCD} = (w + 4)(w + 3)(w - 2) \] **Step 3: Multiply Both Sides by the LCD** \[ (w + 4)(w + 3)(w - 2) \cdot \left( \frac{4}{(w + 4)(w - 2)} + \frac{5}{(w + 3)(w - 2)} \right) = (w + 4)(w + 3)(w - 2) \cdot \frac{4}{(w + 3)(w + 4)} \] Simplifying each term: \[ 4(w + 3) + 5(w + 4) = 4(w - 2) \] **Step 4: Simplify the Equation** \[ 4w + 12 + 5w + 20 = 4w - 8 \] \[ 9w + 32 = 4w - 8 \] \[ 5w + 32 = -8 \] \[ 5w = -40 \] \[ w = -8 \] **Step 5: Check for Validity** Ensure that \( w = -8 \) does not make any denominator zero: - \( w + 4 = -8 + 4 = -4 \neq 0 \) - \( w - 2 = -8 - 2 = -10 \neq 0 \) - \( w + 3 = -8 + 3 = -5 \neq 0 \) All denominators are non-zero, so \( w = -8 \) is a valid solution. **Final Answer:** \[ w = -8 \]

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve the equation \[ \frac{4}{w^{2}+2 w-8}+\frac{5}{w^{2}+w-6}=\frac{4}{w^{2}+7 w+12}, \] we first factor the quadratic expressions in the denominators. 1. **Factoring**: - \( w^2 + 2w - 8 = (w + 4)(w - 2) \) - \( w^2 + w - 6 = (w + 3)(w - 2) \) - \( w^2 + 7w + 12 = (w + 3)(w + 4) \) So, substituting the factored forms, the equation becomes: \[ \frac{4}{(w + 4)(w - 2)} + \frac{5}{(w + 3)(w - 2)} = \frac{4}{(w + 3)(w + 4)}. \] 2. **Finding a common denominator**: The common denominator for the left-hand side is \( (w + 4)(w - 2)(w + 3) \). Rewrite each fraction: \[ \frac{4(w + 3)}{(w + 4)(w - 2)(w + 3)} + \frac{5(w + 4)}{(w + 3)(w - 2)(w + 4)} = \frac{4(w - 2)}{(w + 3)(w + 4)(w - 2)}. \] Hence, the equation simplifies to: \[ 4(w + 3) + 5(w + 4) = 4(w - 2). \] 3. **Expanding and combining like terms**: Expanding both sides gives us: \[ 4w + 12 + 5w + 20 = 4w - 8. \] Combining like terms yields: \[ (4w + 5w + 12 + 20) = 4w - 8 \implies 9w + 32 = 4w - 8. \] 4. **Solving for \( w \)**: Subtract \( 4w \) from both sides: \[ 9w - 4w + 32 = -8, \] which simplifies to: \[ 5w + 32 = -8. \] Now, subtract \( 32 \): \[ 5w = -8 - 32 \implies 5w = -40. \] Finally, divide by \( 5 \): \[ w = -8. \] 5. **Verification**: We need to check if \( w = -8 \) does not make any denominator zero: - \( w^2 + 2w - 8 = (-8)^2 + 2(-8) - 8 = 64 - 16 - 8 = 40 \) (not zero) - \( w^2 + w - 6 = (-8)^2 + (-8) - 6 = 64 - 8 - 6 = 50 \) (not zero) - \( w^2 + 7w + 12 = (-8)^2 + 7(-8) + 12 = 64 - 56 + 12 = 20 \) (not zero) Thus, the solution is \[ \boxed{-8}. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad